Domestic Violence Cases In Jambi: Psychological Factors That Affect Victims to Return Back to Their Offenders - Yurni Yurni (Universitas Batanghari Jambi, 2019)
Most of the domestic violence cases proofed that woman was always be a victim in their own house. Economy will always be the first reason for offenders (husband) to do violence against their wife. Many cases happen but only a few women who have the brave to go to the court to have justice, others choose to keep silent. From these few women, some of them choose to return back to their husband after they see the judge and have sentence for their husband. This study tried to find out psychological factors that may affect women to have reconciliation with their husband. The author performed qualitative analysis on data from interview to four participants who have been consulted their cases on court and experienced domestic violence from their husband. Violence that they got vary from physical such as hitting, punching, and violence using tools (throwing plate or glass to the victim); psychology such as yelling, negative statement, neglected; economy such as not giving money to support their life. Data gained from interview showed that, some victims economically independent, its mean they have their own income but some are dependent; they still need support from their husband as the offender. Negative statement as they daily consumption have been internalized, it made them see their future helpless without husband; children become the other reason why victim choose to recon ciliate, they don’t think they could support their children economically. Social stigma as a widow make them afraid to be separate from their husband. Victims experiencing domestic violence have low self-concept, low self-esteem and low self-image. Those are become main factors that affect them to return back and have reconciliation with their husband. Having no goal setting and direction in their life become minor factors.